VITALITY OF THE LAUJE LANGUAGE ENCLAVE IN THE FAMILY DOMAIN IN TOLITOLI REGENCY - Tamrin, Tamrin; Haliq, Abdul; Marzuki, Abdul Gafur; Fatinah, Siti; Asri B, M. (Universitas Negeri Makassar, 2024)
This research aims to describe the vitality of the Lauje language as an enclave of ethnic minority languages in Tolitoli Regency, Central Sulawesi. The method used is a sociolinguistic approach with questionnaires, interviews, observation, and recording techniques. Next, it was analyzed descriptively based on frequency and percentage calculations and processed using the SPSS program. The results of the analysis show that the vitality of the Lauje language based on age, those aged 40–50 years and those aged over 60 years is still very strong, namely the Lauje language, and those aged under 20 years and those aged 20–39 years are in a position that is vulnerable to decline. Furthermore, the vitality of the Lauje language is based on education; respondents with no school education and stable basic education maintain their Lauje language but have the potential to experience decline. The vitality of the Lauje language in the family domain based on work as farmers is still stable in maintaining its language, and those who work as housewives are still very strong in maintaining their language. The Lauje language is in a safe position. Overall, the vitality of using the Lauje language in the family domain is 0.69, which means that the vitality of the Lauje language in the family domain is in a stable, steady position but has the potential to experience decline.